Access to social rights for temporary labour migrant women in the EU : an intersectional perspective on seasonal and posted workers in France and Spain - Deverson, Audrey (Université de Strasbourg, 2026)
Temporary labour migration constitutes both a historical phenomenon and an enduring central issue within the European Union. This thesis adopts a socio-legal approach to analyse the cases of France and Spain, focusing on seasonal work and posting of workers in the agricultural sector. It examines the experiences of temporary migrant women workers at the intersection of migration law and labour and social security law, in particular with regard to social security. Drawing on an intersectional perspective articulated around the concept of vulnerability, this research highlights the structuring role of law in these women’s experiences. This thesis demonstrates that the applicable legal framework contributes to reinforcing their vulnerability by establishing a system of exclusion and invisibilisation based on migration status, employment status and a gendered and racialised labour division, thereby limiting these women’s effective access to rights linked to their participation in the labour market, such as unemployment benefits, as well as to those relating to their reproductive lives. La migration temporaire de travail constitue à la fois un phénomène historique et un enjeu toujours central au sein de l’Union européenne. Cette thèse analyse, dans une perspective sociojuridique, les cas de la France et de l’Espagne, en se concentrant sur le travail saisonnier et le travail détaché dans le secteur agricole. Elle examine l’expérience des travailleuses migrantes temporaires à l’intersection du droit des migrations et du droit social, notamment en matière de sécurité sociale. Mobilisant une perspective intersectionnelle articulée au concept de vulnérabilité, cette recherche met en lumière le rôle structurant du droit dans l’expérience de ces femmes. La thèse démontre que le cadre juridique applicable contribue à renforcer leur situation de vulnérabilité en instaurant un système d’exclusion et d’invisibilisation fondé sur le statut migratoire, le statut d’emploi, et une division du travail genrée et racialisée, limitant ainsi l’accès effectif de ces femmes aux droits liés à leur participation au marché du travail, tels que le droit au chômage, ainsi qu’à ceux relatifs à leur vie reproductive.
Keywords: Agriculture; Approches sociojuridiques; Droit au chômage; Droit de l’UE; Droits économiques et sociaux; Espagne; European Union law; France; Intersectionality; Intersectionnalité; Justice reproductive; Migration temporaire de travail; Pays de l'Union européenne; Posting of workers; Protection sociale; Reproductive justice; Seasonal work; Social protection; Socio-Legal studies; Spain; Statut juridique; Temporary labour migration; Travail détché; Travail saisonnier; Travailleuses étrangères; Unemployment benefits; Vulnerability; Vulnérabilité; Émigration et immigration

A legal appraisal of the minimum wage policy in the private formal sector and sustainable livelihood in urban centres in Cameroon: the case of Buea - Akamin Asonga, Patrick (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
This paper analyses the minimum wage as an instrument to provide a sustainable livelihood for employees and their families. In addressing this topic, the paper questions whether the present- day minimum wage of the country can actually enhance a sustainable livelihood for workers and their families in urban centres in general, and in the Buea municipality in particular. The paper further examines the relevant international and domestic instruments, such as the ILO Minimum Wage Fixing Convention No. 131 and the 1992 Labour Code of Cameroon. Findings reveal that the current minimum wage, which stands at 43,969 FRS, is grossly inadequate and does not match the prices of basic commodities needed for survival in the country as a whole and in Buea specifically. This, therefore, necessitates an increase in the current minimum wage. Given this situation, workers struggle to attain a sustainable livelihood. A new minimum wage policy considering Cameroon’s current economic situation could alleviate the suffering of these workers. Cet article analyse le salaire minimum en tant qu’instrument permettant d’assurer des moyens de substance durable aux travailleurs et leurs familles. Abordant cette problématique, l’étude s’interroge sur la capacité du salaire minimum actuellement en vigueur dans le pays à garantir effectivement un niveau de vie durable aux travailleurs et à leurs familles dans les centres urbains en général, et dans la municipalité de Buea en particulier. L’article examine en outre les instruments internationaux et nationaux pertinents, tel que la Convention (n° 131) de l’OIT sur la fixation des salaires minima et le Code du travail camerounais de 1992. Les résulta révèlent que le salaire minimum actuel, fixé à 43,969 FCFA est largement insuffisant, et ne correspond pas au coût des produits de première nécessité indispensables à la survie, tant a l’échelle nationale qu’à Buea en particulier. Cette situation rend donc nécessaire une revalorisation du salaire minimum en vigueur. Dans ces conditions, les travailleurs éprouvent de sérieuses difficultés à atteindre des moyens de subsistance durables. L’adoption une nouvelle politique de salaires minimum, tenant compte de la situation économique actuelle du Cameroun, pourrait contribuer à atténuer les souffrances de ces travailleurs.
Keywords: Appréciation juridique; Cameroon; Cameroun; Legal Appraisal; Minimum Wage Policy; Moyens de Substance durables; Politique du salaire minimum; Private Formal Sector; Secteur formels privés; Sustainable Livelihood

Combating trafficking in persons in Africa: efforts and enforcement challenges - Tamfuh, Wilson N.; Awa Njoworia, Valerie Adamu (Revue Africaine des Réflexions Juridiques et Politiques, 2026)
Recently, human trafficking has been on a rise with African states fighting to put an end to the crime by protecting victims, prosecuting culprits and collaborating with other partners. As a giant step towards fighting this crime, many African states ratified the Palermo Protocol, Ouagadougou Action Plan, domesticated trafficking laws and put in place institutions. Despite these efforts, trafficking in persons remain a persistent crime due to conflicts, poverty, unemployment and corruption, which increase the vulnerability of persons within and from Africa. Adopting a doctrinal research method, this paper questions the effectiveness of African States’ efforts to protect, prosecute and prevent this crime in and from Africa. It concludes that, while African states must be applauded for their efforts to protect, prosecute and collaborate with other states and organizations to combat this crime, much still remains to be done. This is due to the existence of factors like poverty, unemployment that create vulnerabilities and enforcement challenges like corruption, victim identification, delays in cross-border collaboration and weak legal frameworks. African states should therefore address underlying socio-economic factors, strengthen their domestic legal frameworks and enhance international cooperation to fully combat this crime. Récemment, la traite des êtres humains a connu une recrudescence, et les États Africains s'efforcent d'y mettre fin en protégeant les victimes, en poursuivant les auteurs et en collaborant avec d'autres partenaires. Dans le cadre de cette lutte, de nombreux États Africains ont ratifié le Protocole de Palerme et le Plan d'action de Ouagadougou, intégré des lois nationales relatives à la traite et mis en place des institutions spécialisées. Malgré ces efforts, la traite des personnes demeure un crime persistant en raison des conflits, de la pauvreté, du chômage et de la corruption, qui accroissent la vulnérabilité des personnes en Afrique et en provenance d'Afrique. Adoptant une méthode de recherche doctrinale, cet article examine l'efficacité des efforts déployés par les États Africains pour protéger, poursuivre et prévenir ce crime sur leur territoire et à partir de leur territoire. Il conclut que, alors que les États Africains doivent être salués pour leurs efforts de protection, de poursuite et de collaboration avec d'autres États et organisations pour combattre ce crime, il reste encore beaucoup à faire. Ceci s'explique par l'existence de facteurs tels que la pauvreté et le chômage, qui créent des vulnérabilités, et par des difficultés d'application de la loi comme la corruption, l'identification des victimes, les retards dans la collaboration transfrontalière et la faiblesse des cadres juridiques. Les États africains devraient donc s'attaquer aux facteurs socio économiques sous-jacents, renforcer leurs cadres juridiques nationaux et intensifier la coopération internationale afin de lutter pleinement contre ce crime.
Keywords: African States; Corruption; Palermo protocol; Pauvreté; Poverty; Protocole de Palerme; Trafficking in persons; Traite des personnes; États Africains

The future of a prohibition on indirect unfair discrimination as part of South African anti-discrimination employment law : a comparative reflection - Huysamen, Elsabe (Stellenbosch University, 2025)
ENGLISH ABSTRACT: The Constitution of the Republic of South Africa, 1996 (“Constitution”) enshrines the right to equality, emphasising “the full and equal enjoyment of all rights and freedoms”. This commitment embodies the principle of substantive equality, which extends beyond mere formal equality by addressing systemic inequities and striving for transformative change. The pursuit of transformative equality is underpinned by two constitutionally mandated mechanisms: affirmative action and the prohibition of unfair discrimination, both direct and indirect. Within this framework, the prohibition of unfair discrimination serves a dual purpose: It establishes a foundation for defending formal equality while simultaneously acting as a transformative tool, particularly in safeguarding against indirect discrimination. In a transformative context, the concept of protection against indirect discrimination specifically is significant as it acknowledges that equal treatment can still perpetuate inequality. The concept has the unique ability to identify hidden barriers and protect against more subtle forms of unfair discrimination, rendering it instrumental in advancing substantive equality and promoting long-term, systemic change. Yet, despite its transformative potential, the application of protection against indirect unfair discrimination in South African employment jurisprudence remains underdeveloped. And even in jurisdictions where the concept has received greater attention (for purposes of this study, the United States of America, Canada and the United Kingdom), it has not significantly advanced substantive workplace transformation. The reasons for this limited success are partly shared across these jurisdictions and partly unique to South Africa. Given the above, the primary objectives of this study are threefold: (i) to explore the protection against indirect discrimination in advancing transformative equality within the South African constitutional framework; (ii) to investigate the reasons for the limited development and application of this concept in South African employment law; and (iii) to assess whether the prohibition of indirect discrimination should be upheld as a distinct legal concept in employment law. These objectives were anchored by the fundamental question guiding the study: what role does the concept stand to play in employment law in SA in future and, if any, to what extent and in what form? The study begins by examining the broader concept of equality – a notion that is both complex and continually evolving. Key questions that are addressed include: What does equality mean? What are the objectives inherent to equality? What values underpin the concept? Following this exploration, the focus shifts to the role of equality within the South African Constitution, specifically the content of the right to equality as provided for in section 9 of the Constitution. This includes an overview of the constitutionally mandated mechanisms for enforcing equality, namely affirmative action and the prohibition of unfair discrimination, with particular attention to protection against indirect forms of unfair discrimination. The study thereafter narrows its focus to the application of the latter concept within South African employment law. It highlights the challenges that have hindered the effective development of the concept, which can be broadly categorised as conceptual and practical obstacles. The South African experience is compared to the development and application of the concept in the United States, Canada, and the United Kingdom, offering a comparative perspective on the concept’s evolution in the aforesaid jurisdictions. The study concludes by presenting suggestions and recommendations on the future role of indirect discrimination within South African anti-discrimination employment law. It also recommends strategies for more effective implementation of the concept.
Keywords: Affirmative action programs; Discrimination in employment; Employment; Labor laws and legislation; Law reform; South Africa; Unfair labor practices

Examining the Impact of Remote Work on Employees, Employers, and the State in Nigeria - Adeyinka, Mutiu Abiodun; Gbajumo-sherrif, Mariam A.; Elegbede, S. Tunde (African Journal of Economic and Business Research, 2025)
Abstract The rise of remote work, accelerated by the COVID-19 pandemic, has created significant challenges for employees, employers, and the government, complicating the management of remote teams while striving to maintain productivity and organizational cohesion. The central problem addressed in this study is the deteriorating state of employment relations marked by downsizing and layoffs, particularly in the private sector in Nigeria. This study aims to analyze the impact of remote work on these stakeholders through a systematic and thematic review based on PRISMA guidelines. Twenty four publications from 2013 to 2023 were reviewed, sourced from Google Scholar, DOAJ, Scopus, and Web of Science. The findings indicate that while organizations are beginning to adopt tools for remote work and virtual communication, these resources are primarily accessible to larger companies due to associated costs. Additionally, the study highlights the pressing need for enhanced infrastructure and structural improvements to support remote work at a societal and economic level. In conclusion, the study recommends that the government enhance infrastructural development and that organizations implement better strategies for remote work. Furthermore, individuals should pursue advancements in technology to adapt to the changing landscape. These recommendations aim to promote sustainable employment relations and economic development in Nigeria in light of the evolving digital economy.
Keywords: Employees; Employment Relations; Government; Remote Work

Proposed legal reforms to protect South Africa's informal social security - Zeelie, Robin Erin (University of Pretoria, 2024)
Informal social security is a non-governmental form of social security between kin and/or community members and is a prevalent practice in South Africa. The question this dissertation analyses is whether the South African government fails in its constitutional duty to protect and advance informal social security. The dissertation limits itself to analysing cash transfers through social grants, and social insurance in the Unemployment Insurance Act and the Compensation for Occupational Injuries and Diseases Act. This dissertation delineates its definition of informal social security, historically contextualises its practice, and explains the contemporary formal social security framework. This dissertation finds five prominent shortcomings in the formal framework, and that these shortcomings have a profoundly negative, weakening effect on informal social security, as the more people who rely on informal mechanisms, the less it can respond to needs arising from life contingencies, shocks, and risks. The dissertation concludes by analysing three legal reform proposals the state can implement: extending existing social insurance frameworks to those in the informal sector, promoting cooperatives as a formal platform for the informal, and the basic income grant.
Keywords: Basic income grant; Cooperatives; Duty; History; Informal social security; Republic of South Africa; Social assistance; Social security

Compliance with decent work standards by multinational enterprises - Maluleke, Tirhani Foster (University of Pretoria, 2024)
In contemporary times, the issue of human and labour rights violations has gained significant momentum, rendering it imperative for international organisations, states, and businesses to address this critical concern. It is widely acknowledged that while multinational enterprises can aid in achieving economic growth by investing directly overseas and raising the standard of living for the residents of host nations, their business operations may also result in abuse of human and labour rights. The United Nations (UN) Charter was drafted to set forth obligations for individual states, yet businesses do not bear international legal obligations. The Universal Declaration on Human Rights was adopted to implement the substantive contents of human rights referred to in the UN Charter in the general way. The preamble of the Universal Declaration refers to all organs of society, but, at the time of its adoption, businesses were not considered among such organs. It was inconceivable that business organisations would become so economically powerful within a few decades that they would pose a significant risk to human and labour rights, which would not be easily regulated under the national law of their host nations. It is the hypothesis of this study that numerous multinational enterprises (MNEs) violate core human and core labour rights, and that the existing regulatory framework does not adequately regulate them. To prove this hypothesis, this thesis will adopt a two phased approach. Firstly, a careful case law and literature review will reveal the inadequate regulation of MNEs. Evidence suggests that MNEs are guilty of flagrant labour standards and human rights violations. As a result of globalisation, MNEs have gained stronger international influence, and they are able to move their businesses to countries with low cost of labour and less regulations. This phenomenon weakens the governments of host nations as they are keen to promote foreign direct investment in order to reduce unemployment and to ensure economic growth. As a result, the host nations are encouraged to set laws that will attract MNEs at the expense of human and core labour rights. As result, MNEs are not held accountable in respect of their violation of human and labour rights. Secondly, this thesis will assess the efficacy of the regulatory instruments developed by the international community in response to the mentioned problem. This aspect is covered in Chapter 3 to 7 of this thesis. The strategies include the public and private hard law and soft law mechanisms developed at international level as well as campaigns by Non-Governmental Organisations (NGOs). Based on evidence, this thesis will conclude that a soft law approach is not fully effective. As such, Chapter 8 of this thesis proposes the introduction of some hard law measures to improve the existing soft law instruments to augment the existing legislative frameworks of the host countries. In particular, the thesis recommends regulatory reforms, which will empower the International Labour Organisation to intervene to prevent the labour rights violations by MNEs and where such violations occur, to at least provide effective remedies to vulnerable employees. This thesis constitutes a theoretical study, which attempts to provide suggestions regarding the implementation of realistic measures, which if implemented, may contribute to the attainment of decent work for all men and women who are engaged in work for MNEs.
Keywords: Codes of conduct; Decent work; Hard law; Human rights; Human rights due diligence; ILO MNE declaration; International Labour Organisation; International framework agreements; Labour rights; Multinational enterprises; OECD guidelines; Regional free trade agreements; Soft law

Employee’s Pilferage and Security in Beverage Manufacturing Companies in Lagos State, Nigeria - Attah, Edwin; Abdullahi, Liman; Yusuf, Usman (African Journal of Politics and Administrative Studies, 2024)
The purpose of this paper is to examine the relationship between employee pilferage of pilferage and security in beverage manufacturing companies in Lagos State. The study is anchored on the rational choice theory in order to understand the connection between pilferage and security in beverage manufacturing companies in Lagos State. The researcher adopted a mixed research method involving survey research and historical research designs. The population of this study is 8,595 staff. This comprises all employees of Promasidor Nigeria Ltd, Nigeria Bottling Company (Coca Cola), Cadbury Nigeria Plc, and Guiness Nigeria Plc. The sample size of the study was 400 determined using Rakesh Sample size formula. Data were collected from primary and secondary sources. Primary data were collected using questionnaires, while secondary data were collected from related works on pilferage and security in beverage manufacturing companies. Data collected from questionnaire were analyzed using absolute frequencies and simple percentages, while data from secondary sources were analyzed using relational-content analysis. Among other things, it was found that the higher the level of pilferage, the lower the level of security of employees in beverage manufacturing companies in Lagos State. Among other things, it was recommended that given that there is relationship between pilferage and security in beverage manufacturing companies in Lagos State, beverage manufacturing companies in the state should ensure that stealing is drastically reduced in their various organizations through employment, training and proper motivation of staff who must be full-time staff. This would largely make the employees committed to work and shun pilferage.
Keywords: Pilferage; companies; employee; manufacturing; security

A comparative legal analysis of the accommodation of neurodiversity in the workplace : towards a universal right to reasonable accommodation - Conradie, Riana (Stellenbosch University, 2024)
Workforces are made up of individuals with differences in personal characteristics, differences that may be traced back to unique personality types and traits and – sometimes – neurodivergence. Due to the inherent subjectivity of the interpersonal relationships that form the foundation of a work environment, these differences in personal characteristics inevitably lead to tension. In addition, as part of managing a work environment employers frequently take decisions that may be influenced by views and perceptions regarding employees’ personal characteristics. This study starts with a descriptive examination of the meaning of personality and the influence that personality traits and types may have on employment. This is followed by a descriptive examination of neurodivergence, the various forms of neurodivergence, and the impact of these conditions on the work environment. Building on these descriptive and conceptual underpinnings, the legal implications of neurodiversity in the workplace are investigated by identifying which principles of the existing South African employment law framework may be utilised to provide protection and promote respect for neurodiversity and the neurodiverse differences between employees. This encompasses a discussion of the South African employment law rules relating to recruitment and selection of employees, some of the rules applicable to the day-to-day management of employees, and the rules relating to termination of employment that may be (in)directly influenced by considerations of neurodiversity. The focus thereafter shifts to consider the legal principles of employment discrimination law, where it is found that the listed ground of disability and an unlisted arbitrary ground may potentially be used as the applicable grounds of discrimination by employees if they are prejudiced due to their neurodiverse characteristics. In addition, the possibility that the rules on reasonable accommodation may be utilised as primary mechanism to properly regulate neurodiversity in the work environment and protect against prejudicial treatment of employees due to their inherent personal neurodiverse characteristics is also considered. The South African position and potential employment law rules that may apply to the management of neurodiversity in the work environment is compared to the position in the United Kingdom by focusing on the meaning of disability, the right to reasonable adjustments, and the right to request flexible working arrangements. Finally, the conclusions that may be drawn from this study are emphasised and are followed by some recommendations on how (reasonable) accommodation of neurodiversity in the work environment may appropriately be used as primary mechanism to provide employees with sufficient and appropriate protection of differences in neurodiverse characteristics. Even though this study focuses on neurodiversity and neurological differences between employees, the principles and recommendations from this study may be of value in relation to the appropriate management and regulation of all inherent differences between employees.
Keywords: Discrimination in employment; Diversity in the workplace; Employment; Labor laws and legislation; Neurodivergent people; Neurodiversity; People with disabilities

The legitimacy of dismissals for off-duty misconduct in South African labour law - Phulu, Thandekile (University of Pretoria, 2024)
The main aim of this thesis is to solve the uncertainties brought about by dismissals for off-duty misconduct. First, it should be acknowledged that the world as we know it has changed and continues to evolve. Dismissals have been significantly impacted by the use of social media outside the workplace. The legalisation of the use of cannabis by an adult person has also brought uncertainties in the way dismissals are handled, especially in cases where an employee consumes cannabis off-duty. These two aspects have significantly influenced dismissals for off-duty misconduct in South Africa, with employees alleging that their rights to privacy, dignity and freedom of expression are infringed. The thesis reveals that regardless of these modern changes, off-duty misconduct dismissal is still governed by the generic provisions of the Labour Relations Act 1995 and its Code of Good Practice: Dismissal. The thesis underscores the lack of clarity regarding the regulation of dismissals for off-duty misconduct in South Africa. Furthermore, despite the judiciary’s establishment of tests (the nexus test and the breakdown of the employment relationship), challenges in adjudicating off-duty misconduct cases persist. This thesis analyses the South African legal framework governing dismissals for off-duty misconduct. The research investigates the evolution of South African dismissal law, tracing its development from the pre-democratic era to the post-democratic era. This investigation scrutinises the shifts in the legal landscape regarding dismissals for off-duty misconduct. The analysis encompasses a range of legal instruments pertinent to South Africa, including legislation, international law, common law, and judicial precedent. The current need for a Code of Good Practice for off-duty misconduct dismissal is highlighted. This rationale is prompted by a comparative examination of other countries where, despite the absence of specific codes addressing off-duty misconduct, a proactive stance has been adopted to safeguard employees’ off-duty rights by enacting relevant legislation. These chosen states have statutes regulating employees’ off-duty conduct and clarifying which conduct is protected and in which circumstances. Consequently, the thesis proposes a Code of Good Practice: Dismissal for Off-duty Misconduct. This Code would assist in the uniformity of application of relevant aspects in determining the fairness of dismissals for off-duty misconduct, thus alleviating labour suits concerning this type of dismissal. The Code would also provide employers with guidelines on how to draft off-duty misconduct policies without infringing employees’ constitutional rights.
URI: https://repository.up.ac.za/handle/2263/97021
Keywords: Cannabis use; Dismissal; Labour law; Misconduct; Off-duty; Social media; South Africa

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Accepted: 2024-04-08T07:03:10Z
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition

Attaining effective and speedy resolutions of unfair dismissal disputes in Lesotho: An explorarion of possible lessons from South Africa - Ntaitsane, Mamolefi Anacletta (National University of Lesotho, 2023)
National Manpower Development Secretariat
Keywords: Labour dispute; Lesotho; Resolution mechanisms; Unfair dismissal disputes

Structural Change, Productivity Growth and Labour Market Turbulence in Sub-Saharan Africa - Mensah, Emmanuel; Owusu, Solomon; Foster-McGregor, Neil; Szirmai, Adam (Journal of African Economies, 2023)
This paper presents a shift-share decomposition of the role of structural change in driving labour productivity in sub-Saharan Africa (SSA). The paper further examines the effect that the observed structural change has had upon the dynamics of labour markets in SSA. The analysis is based on a newly constructed dataset, the Extended Africa Sector Database. This database updates and extends the Africa Sector Database of the Groningen Growth and Development Centre. It includes eighteen countries covering the period 1960–2015. Overall, the database shows that productivity growth has been slow, with large and persistent sectoral productivity gaps present. The extent of structural change has been higher than that observed in previous studies, however. But while the share of employment and value added in agriculture has declined, resources have been pulled into certain service sectors that have relatively low productivity, thus limiting aggregate productivity improvements. The general direction of structural change has not been towards the most productive sectors. Results of the labour market analysis complement this analysis, providing suggestive evidence of a role for labour market institutional arrangements in many SSA countries in affecting these outcomes.

Exploring the Voice of Populist Movements in the Employment of Foreign Nationals: A Comparative Study of Botswana and South Africa - Utete, Reward; Zhou, Sheunesu; Ajani, Oluwatoyin Ayodele (International Journal of Social Science Research and Review, 2023)
Labour immigration has been on the rise and has had policy implications for public leaders of relatively stable Southern African Development Corporation (SADC) countries. In this paper, the status of populism and labour immigration in Botswana and South Africa was explored. The primary sources of labour immigration are Zimbabwe and Mozambique. Economic disparities and the disintegration of the socio-economic conditions of the neighbouring countries have been major antecedents for the labour movements of the masses. The study utilised a qualitative method and comparative case study design. The study found that populist movements have much influence on the termination of employment of foreign nationals in Botswana and South Africa as shown by their anti-immigrant attitudes, market protectionism, and close-the-borders protests. As these measures have become inefficient over the years, policies and proposals are recommended in response.
Keywords: Economy; Employment; Foreign Nationals; Immigrants; Policies; Populist Movements

The legal regulation of trade union recognition in South Africa in historical and comparative context - Germishuys-Burchell, Wilhelmina (Stellenbosch University, 2023)
This study investigates the impact and importance of the legal regulation of trade union recognition and associated challenges in South Africa. It evaluates the current regulation of trade union recognition, including legislation and judicial attitudes apparent from the interpretation, application, and enforcement of such legislation, to ascertain its continued appropriateness in the current South African industrial relations environment. The study considers the policy choices of both voluntarism and majoritarianism underlying the Labour Relations Act 66 of 1995 (“LRA”) and the “workplace” constituency to which it applies as factors that might be contributing to challenges experienced in the current regulation of collective bargaining in South Africa. It evaluates the current model of trade union recognition and representativeness as it applies to the acquisition by trade unions of organisational rights, collective bargaining rights and trade union recognition for purposes of retrenchment consultation. It recognises that the specific model chosen to regulate the representative status of trade unions has a significant effect on the ability of trade unions to organise and conclude collective agreements and, as such, on the distributive effects of such agreements in the labour market and broader society. The study commences with an historical overview of the regulation of trade union recognition under the 1956 LRA and thereafter considers the 1995 LRA as a product of criticism against the 1956 LRA. Specific issues considered, largely based on the analysis of the relevant decisions by the Constitutional Court, include the following: the impact of Constitutional Court jurisprudence relating to trade union recognition on the process of collective bargaining and on the legal regulation of the right to strike; the role of representativeness and its link with the workplace as the constituency for recognition and acquisition of organisational rights; the often winner-takes-all effect of the current model on collective bargaining as a major cause of labour unrest; the reactive role the legislature has played over the past, almost three decades to address challenges; the extent to which intervention should take place to safeguard the institution of collective bargaining from being undermined as well as the regulation of collective agreements as the product of collective bargaining and as the primary source of terms and conditions of employment. The comparative review of Canadian law focuses on a number of issues selected specifically for their potential to provide insights into how the weaknesses in South African regulation may be remedied. This includes insights into the accommodation of special or significant minority interests and how to address recognition in the context of multi-location employers. The thesis concludes with remarks on the insights gained from the Canadian model and the 1956 LRA. Where appropriate, suggestions are made on the way forward for South Africa as to the appropriate regulation of trade union recognition and representativeness.
URI: http://hdl.handle.net/10019.1/127125
Keywords: Collective bargaining; Collective labor agreements; Dismissal of employees; Employee rights; Industrial laws and legislation; Labor disputes; Labor unions; South Africa

Effective strategies for resolving labour disputes in the corporate sector: Lessons from Nigeria and the United States - Uzougbo, Ngozi Samuel; Akagha, Onyinyechi Vivian; Coker, Julie Olajumoke; Bakare, Seun Solomon; Ijiga, Amina Catherine (World Journal of Advanced Research and Reviews, 2023)
The relationship between an employer and employee though governed by various laws and regulations can still at some point witness some disagreements and dispute. Labour disputes are not uncommon neither are they peculiar to a particular industry in a country. Usually, trade disputes are hinged on agitation of employees for compensation, good working conditions, job stability and agitation against unlawful termination or dismissal of from service. Over the years, employees have adopted different ways to exhibit their discomfort and grievances in order to convey their message such as strike actions, peaceful protest and so on. There’s no doubt that these disputes will drastically reduce the level of productivity and overall beneficial impact of the industries in the economic growth of the country. Hence, there’s a need to adopt strategies for resolving these labour disputes. Some industries have applied round table discussions, arbitration, mediation, collective bargaining as well as grievances remedial processes. This work will provide an overview of the causes of disputes in the corporate sector, examine the features of the Nigerian and United States disputes resolution system and also juxtapose the strategies for resolving labour disputes in the two countries. Furthermore, it will provide recommendations to effectively addressing labour issues within the business sector.
Keywords: ADR; Alternative dispute resolution; Industrial relations; Legislative Framework; Multi-door courthouse; Trade unions

The protection of the national labour force against foreign competition under labour migration laws and policies : a comparative analysis between the Democratic Republic of Congo and South Africa - Kamwimbi, Kasongo Theodore (University of South Africa, 2022)
Labour migration, which involves both labour immigration and labour emigration, refers to ‘the cross-border movement of people from a homeland to a location outside that homeland, with the purpose of taking up employment’.1 Labour migration has become an ever more important feature of the globalising world as it plays an important role and has a direct impact on African countries’ economies and societies. Recognising the significant benefits of labour migration to countries of origin and destination, the African Union urges African States to enact labour migration laws, regulations, and policies in a regular, transparent, and comprehensive manner at both continental and country levels. In this regard, many African countries have exercised their prerogative to regulate labour migration, which falls within each state’s sovereign discretion. By way of illustration, this thesis focuses on two specific countries, namely the Democratic Republic of Congo (DRC) and South Africa, which have regulated the employment of foreign-born workers. The two countries have established a legal and regulatory framework aimed at protecting the national labour force against foreign competition. The two countries have been selected for this study because they are comparable in many ways while differing as much as possible in terms of the institutional set-up of their migration systems and labour markets. In fact, this study seeks to compare the DRC’s and South Africa’s labour migration laws, regulations and policies, particularly how these legal and regulatory instruments effectively protect the national labour force against foreign competition. In this sense, the study explores the overall successes and challenges of these legislative and regulatory endeavours, while identifying the shortcomings and merits of the implementation of the laws and policies in the two countries.
Keywords: Congo (Democratic Republic); Contract of employment; Emigration and immigration law; Foreign workers; Labor laws and legislation; Labour market; Manpower policy; Migrant workers; South Africa

A comprehensive analysis of the law regulating equal pay in South Africa - Ebrahim, Shamier (University of South Africa, 2022)
The purpose of this thesis is as follows. Firstly, to identify the problems associated with the causes of action in section 6(4) of the EEA; the onus in section 11 of the EEA; the right to access pay related information; the grounds of justification in section 6(2) of the EEA and the Employment Equity Regulations; the equal pay provisions in sections 198A-198C of the LRA; and section 27 of the EEA. Secondly, to discuss and analyse the South African equal pay legal framework in order to provide answers and solutions to the research problems. Thirdly, to discuss and analyse the international legal framework regulating equal pay and the United Kingdom equal pay law in order to provide answers to the research questions to the extent and breadth called for. Fourthly, to summarise the answers to the research questions as sourced from South African law, international labour law and the United Kingdom equal pay law.
Keywords: Comparator; Equal pay claims; Equal pay for substantially the same work; Equal pay for the same work; Equal pay relating to non-standard (atypical) employees; Grounds of justification; Hypothetical comparator; Onus in section 11 of the EEA; Right to access pay-related information; Same employer; Section 27 of the EEA; Section 6(4) of the EEA; Sections 198A-198C of the LRA; Subordinate comparator; Terms and conditions of employment

The rising role of China and Chinese enterprises in transnational labour law: Theoretical inquiries and case studies in the context of Chinese outward mining investment in Africa - Chen, Si (McGill University, 2022)
Transnational labour law scholarship has emerged over the past three decades. However, relatively limited scholarship has explored the role of actors from emerging market economies and the challenges and opportunities they have brought for achieving decent work in a globalized economy. This thesis addresses the research gap through an in-depth investigation into the role of actors from China in the dynamics of multi-level governance of labour rights in a globalized economy. Building on a multi-level, actor-centred and processual approach, this thesis argues that China and Chinese enterprises are playing a rising role in developing and shaping the dynamics of multi-level governance of labour rights in the global cobalt supply chain. Furthermore, the thesis suggests that actors from China have started challenging some unequal patterns of existing labour governance in the global cobalt supply chain and have demonstrated the potential to form a counterbalancing force to challenge the dominant role of actors from the global North. A multi-level governance framework has recently emerged and rapidly evolved in the global cobalt supply chain to eliminate child labour in the artisanal copper-cobalt mining sector in the Democratic Republic of the Congo. This framework is complex, pluralistic, and decentred. A wide range of state and non-state actors are developing various governance initiatives and shaping the dynamics of multi-level governance. Actors from China are playing a rising role in the global cobalt supply chain alongside a few other actors that have also provided proposals from the global South. Over the past decade, Chinese state agencies, nationwide industry associations and mining enterprises have proactively engaged in developing and shaping the multi-level governance framework to address governance deficits on decent work in the global cobalt supply chain. State agencies have developed various regulatory documents to enhance the social dimension of the Chinese regulatory framework for outward foreign direct investment. Nationwide industry associations have further conceptualized the term “corporate social responsibility” and have taken labour rights as key to the social responsibilities of Chinese enterprises operating overseas. Specifically, a Chinese nationwide industry association for the mining industry has developed comprehensive guidelines and initiatives to clarify and operationalize the labour component of social responsibilities in Chinese outward mining investment. The changing dynamics of multi-level governance have played a crucial role in shaping the private labour governance initiatives that Chinese mining enterprises are developing in the global cobalt supply chain. The contributions of this thesis are original, significant, and timely, given the notable research gaps on China and Chinese enterprises’ engagement with the dynamics of multi-level governance of labour rights in a globalized economy and the ongoing development of a multi-level governance framework in the global cobalt supply chain
Identifier: https://escholarship.mcgill.ca/concern/theses/7d2790853
Keywords: Chinese enterprise; Droit du travail; Investment in Africa; Labour law; Transnational labour law

The job security of employees of financially distressed companies - Loubser, Mieka E.; Garbers, Christoph (South African Mercantile Law Journal, 2021)
This contribution considers the legislative regulation of the job security (which boils down to preservation of employment) of employees in case of financial distress of a company. It juxtaposes the legislative regulation of four interrelated processes a company may engage in where it finds itself in financial distress, namely a voluntary internal restructuring (especially retrenchment), the transfer of the business or part of the business, business rescue and winding up. The legislative endeavour to preserve the job security of employees in all these processes is described and analysed. The discussion shows that room exists for companies to circumvent this protection and, to the extent that the protection does apply, that it remains difficult for employees to ultimately challenge the substance of decisions negatively affecting their job security. The main protection for employees in all these processes is procedural in nature and to be found in their rights to be informed of and consulted prior to decisions negatively affecting them. In this regard, business rescue is the most employee-friendly process. Participation in this process by employees, however, requires a fine balance as it may be self-defeating and lead to winding up and the permanent loss of jobs.
Keywords: Business rescue; Dismissal; Insolvency; Job security; Labor laws and legislation; Liquidation; Merger; Operational requirements; Retrenchments; Transfer of a business

Optimising the legal regulation of circular labour migration between South Africa, Lesotho and Zimbabwe - Matete, P. (North-West University, 2021)
Circular labour migration is steadily gaining prominence the world over, primarily due to the benefits it offers to the migrants, to the sending country, and to the receiving country – the so-called "triple-win" benefits. In order to enhance the benefits of circular labour migration, both the International Labour Organisation and the International Organisation for Migration recommend that adequate instruments of governance should be utilised. From the outset, this thesis recognises bilateral labour arrangements as the ideal instruments for enhancing the potential benefits that circular labour migration offers to the stakeholders involved in the process. As far as could be established, there has been no comprehensive research that seeks to provide insights on how the selected countries in the Southern Africa Development Community (South Africa, Lesotho and Zimbabwe) could optimise the benefits of circular labour migration for all stakeholders, primarily through the use of bilateral labour arrangements. The need for these insights in Southern Africa is pertinent due to the absence of a contemporary and clear framework regulating circular labour migration in the region. Based on the foregoing, this thesis advances the proposition that the guidelines provided by international law and standards of labour migration, and the best practices in Spain and New Zealand, can provide significant insights on how South Africa, Lesotho and Zimbabwe can enhance the regulation of circular labour migration to provide optimised benefits for all stakeholders. Proceeding from the above premise, this thesis makes a number of findings. These include the affirmation that bilateral labour arrangements are indeed the key regulatory instruments for promoting the triple-win benefits that circular labour migration offers; that circular labour migration, if managed well, plays an instrumental role in development in both the sending countries and the receiving countries; and that three key areas should be addressed in bilateral labour arrangements in order to effectively promote triple-win benefits. The three key areas that need to be addressed in bilateral labour arrangements in order to enhance the benefits for all stakeholders are linking migration with development, migration governance, and the protection of the rights of migrant workers. This thesis outlines the various principles that are necessary to give effect to these three key areas. This thesis finds that, based on the guidelines provided by international law and standards, it is essential that bilateral labour arrangements, at the minimum, incorporate provisions that facilitate skills training, the return and reintegration of migrants, the transfer of remittances, and the promotion of human resources development. In this regard, this study finds that the bilateral labour arrangements between South Africa and its neighbours, Lesotho and Zimbabwe, fall short of the guidelines provided by international law and standards on labour migration and by the best practices in New Zealand and Spain. The original contribution of this study lies in it being the first study to comprehensively explore the legal measures that South Africa, Lesotho and Zimbabwe could utilise to optimise the regulation of circular labour migration to South Africa as the main receiving country in SADC. This study makes recommendations on how the labour migration legal framework between the three countries can be improved, based on lessons learned from international law and standards on labour migration and best practices from selected countries.
Keywords: Bilateral arrangements; Circular labour migration; Droit du travail; Labour law; Migrant workers; Remittances; Travailleur migrant

Re-integration, rehabilitation and return-to-work of disabled workers : a comparative legal enquiry - Gresse, E. (North-West University, 2020)
There are many employment positions in the labour market that could be filled by the disabled of whom most, given the right environment, could be productive in the workplace. However, there are employers who still labour under the misconception that Persons with Disabilities (PWDs) are unqualified and unproductive although their participation in the workplace could contribute to the national economy, while restoring their dignity and social integration. The United Nations Convention on the Rights of Persons with Disabilities (CRPD) entered into force on 3 May 2008. The CRPD is the first international legally binding treaty aimed specifically at protecting the rights of PWDs. It is expected of ratifying States Parties to either amend their domestic existing laws or to enact new legislation in order to meet their obligations, as set out in the CRPD. In 2008, South Africa ratified the CRPD and the Optional Protocol, thus committing itself to the provisions relating to, inter alia, workplace integration. Article 26 of the Convention mandates States Parties to take effective and appropriate measures to enable PWDs to attain and maintain maximum independence, physical, mental, social and vocational ability, and to ensure their social inclusion. Article 27 stipulates, inter alia, that States Parties shall safeguard and promote the realisation of the right to work, including those who incur a disability during the course of employment. Legislation should make provision for, inter alia the following: • enable PWDs to have effective access to general technical and vocational guidance programmes; • placement services and continued vocational training; • promote employment opportunities and career advancement; • assistance in sourcing, obtaining, maintaining and returning to work; and • reasonable accommodation in the workplace as well as vocational and professional rehabilitation. Although the Compensation for Occupational Injuries and Diseases Act 130 of 1993 was amended recently to include rehabilitation, re-integration and return to work (RTW) as part of its objectives, it will be argued that South Africa needs to initiate targeted legislation and policies that make disability management functions mandatory. Employers’ obligations need to be set out clearly in the Act, because, as it stands, the following lacunae exist: • There is no obligation to appoint Case Managers; • Dismissal protection is not provided for; • The regulation of negative incentives to assist with RTW compliance is lacking; and • The roles of different stakeholders in the RTW process require clarification. Without South Africa having an appropriate and detailed RTW framework, ill or injured employees stand the risk of losing their jobs and becoming dependent on family members and/or disability grants. Against this background, a comparative analysis of international and regional law and the RTW practices of two foreign jurisdictions were made. This enabled the author to devise recommendations and identify the roles of the government, employers, employees and Case Managers. The primary objective of this thesis is to determine how and to what extent regional and international standards and RTW programmes in other countries could assist in developing and amending the current legislative and policy framework in South Africa to promote the RTW of disabled employees.
Keywords: Disability management; Persons with Disabilities; Re-integration; Rehabilitation; Return to work

Portability of social security benefits of circular migrant workers in selected SADC member states - Masoebe, P. (North-West University, 2020)
The issue of portability of social security benefits is a daunting issue facing migrant workers in both Southern Africa and the world in general. In the Southern African Development Community region migration seems to be driven mainly by the need to attain economic freedom. The fact of the matter is that migrant workers from Lesotho and Swaziland who work and have worked in South Africa do play a major role in boosting these countries’ economies. Another issue that cannot be ignored is the fact that circular migration as a phenomenon is unlikely to come to an end any time soon in this part of the world. This means that social security benefits of migrant workers and its portability should be an issue that is dealt with cautiously and speedily, especially in terms of looking at the millions of unclaimed social security benefits reported each year by social security funds and schemes in South Africa. While examining the extent to which selected SADC member states, namely Lesotho, Swaziland and South Africa, have undertaken to combat this issue, international and regional instruments that have a bearing on social security rights are analysed and the realisation is that in as much as these do provide for social security rights and portability of benefits thereof, a lack of ratification and implementation play a vital role in achieving efficient portability of these rights. Although South Africa, as the largest migrant-receiving country in the SADC region, does provide for the right to social security in its Constitution, the fragmented nature of its social security framework, together with other factors such lack of information, exploitation by employers, distances travelled to lay claims and a non-existent social security adjudication system means that migrant workers are normally left with lack of redress when their contracts of employment reach an end. On the other hand, Swaziland and Lesotho, as migrant-sending countries, do not even have provisions in their constitutions that specifically deal with the right to social security. This means that citizens who work abroad do not have sufficient social security coverage in either country, as well as in South Africa as a host country. Consequently, multilateral and bilateral agreements on social security are pivotal in addressing this issue of unclaimed social security benefits as they go a long way in making sure that migrant workers are provided with adequate social security protection and coverage as a whole. Migrant sending countries also need to undertake unilateral initiatives to guarantee that their citizens are adequately protected in this specific sphere of social security. Examples are further drawn from the best practices of different regions in the world, namely the Southeast Asian Nations Region, Caribbean Community and Common Market and the Southern Common Market. The above-mentioned regions have established multilateral social security agreements that seek social security protection for migrant workers who play an undeniable role in their economies. Bilateral social security agreements between Zambia and Malawi, together with the one between Sweden and Philippines, are taken into consideration as best practices that Lesotho, Swaziland and South Africa may draw examples from when drawing up and concluding their own bilateral social security agreements. The Philippines’ unilateral initiatives are also discussed and hailed as the best practices that migrant-sending countries such as Lesotho and Swaziland may further draw examples from. The Philippines has developed strategies aimed at guaranteeing social protection for its migrant workers abroad and further makes sure that it enters into bilateral agreements with any country that receives services from its citizens. While the need to conclude multilateral and bilateral agreements on social security cannot be denied, there is also a need for migrant-sending countries to come up with unilateral initiatives to lessen the burden on migrant-receiving countries in this social security domain. Sectors such as the mining sector should also have mining-specific agreements that specifically deal with issues related to migrant mine workers. Lack of statistics of migrant workers moving in and out of South Africa has also been labelled as one of the reasons halting access and portability of social security benefits; hence there is a need to develop a data-base aimed at keeping track of all migrant workers, retired and otherwise. Migrant workers who seek redress regarding access of their unclaimed or unpaid social security benefits also have to be provided with comprehensive protection from the courts of law. This therefore means that an adjudication system should be established to deal with social security woes so that those seeking redress have adequate legal support.
Keywords: Labour and social protection; Migrant workers; Multilateral agreements; SADC; SADEC; Social protection; Social security; Sécurité sociale; Travailleur migrant

An appraisal of the provision of "benefits" as an unfair labour practice in South African labour law - Newaj, Kamalesh (University of Pretoria, 2019)
This thesis seeks to resolve the ambiguities surrounding the use of the unfair labour practice relating to the provision of “benefits” as a dispute resolution mechanism in South African labour law. This mechanism has been plagued with uncertainty, primar-ily because of the lack of a statutory definition of benefits. Evidently, the interpretation and application of benefits have been left to the courts, resulting in two diverse ap-proaches being endorsed. The first one sought to confer a narrow connotation on ben-efits, the rationale being to separate benefits from the definition of “remuneration”. It further sought to limit the use of this unfair labour practice to instances where the benefit claimed was exclusively provided for ex contractu or ex lege. The primary ob-jective was to protect the divide between disputes of right and disputes of interest, a distinction that is recognised and encouraged in our law. The second approach was one that fostered an expansive interpretation of the term, deeming it to be part of re-muneration. Needless to say it resulted in countless items being subject to determina-tion as benefit disputes. Furthermore, it extended benefits beyond those rooted in con-tract or legislation, including those granted or offered subject to the exercise of mana-gerial discretion. The supplementary challenges firstly relate to the absence of statutory direction on the standards of fairness to be applied in evaluating employer conduct. Secondly, the judiciary has provided opportunities for employees to utilise recourse other than the unfair labour practice provisions to address benefit disputes. Such leeway comes in the form of contractual recourse as well as the ability to institute strike action. In search of solutions to the problems identified above, the study explores and anal-yses the history of the unfair labour practice concept. Thereafter, an extensive exam-ination of the developments in this area of the law is undertaken. This includes a com-prehensive analysis of legislation, case law and academic writings. Having docu-mented and analysed the South African position both pre- and post-democracy, the study critically evaluates these sources of law. The study further involves a diagnostic assessment of international legal instruments and foreign law in order to extract best practices. The conclusions reached are, firstly, that an expansive interpretation of benefits is warranted. This is in line with a purposive interpretation of the LRA, which promotes the constitutional right to fair labour practices and international law. This study there-fore proposes a wide-ranging definition of the term benefits. Secondly, standards of substantive and procedural fairness have been found to be applicable in evaluating employer conduct. As such, fairness guidelines based on these standards have been developed. Thirdly, in respect of the alternate avenues available to resolve benefit disputes, it has been found that although there are strong indicators that point to a conclusion that contractual recourse has been supplanted by statutory recourse, such a finding cannot be definitively made. Furthermore, section 64(4) as it stands provides for the right to strike over unilateral changes to terms and conditions of employment, which includes unilateral changes to pre-existing benefits. However, the judiciary can limit the use of this section in benefit disputes by prioritising the substance of the dis-pute over its form. This thesis ultimately proposes the incorporation of a Code of Good Practice into the LRA. The Code of Good Practice: Benefits adopts the principal research findings of this study. It encourages the enforcement of benefit disputes through the dispute res-olution institutions set up by the LRA. The adoption of this Code (The Code of Good Practice: Benefits) will bring certitude to this field of labour law.
URI: https://repository.up.ac.za/handle/2263/72658
Keywords: Labour law; Labour practice; South Africa

The regulation of non-standard employment in Southern Africa : the case of South Africa with reference to several other SADC countries - Mokofe, William Manga (University of South Africa, 2018)
This doctoral thesis deals with the regulation of non-standard employment in Southern Africa: the case of South Africa with reference to several other SADC countries. The growth and presence of non-standard employment since the 1970s has revealed an important concern in a number of countries, both at the global and national levels. The overall significance of non-standard employment has increased in recent decades in both developed and developing states, as its use has grown exponentially across economic sectors and employment. Non-standard employment is the opposite of the standard employment relationship, which is work that is full time and indefinite. Non-standard employment includes an unequal employment relationship between an employee and an employer. Some workers choose to work in non-standard employment, and the choice has positive results. Nonetheless, for the majority of workers, non-standard employment is associated with job insecurity, exploitation, and the absence of trade unions and collective bargaining. Non-standard employment can also create challenges for firms, the labour market and the economy, including society at large. Backing decent work for all entails a comprehensive understanding of non-standard employment and its ramifications. This study explores the regulation and protection of non-standard employment in Southern Africa with focus on South Africa. The study draws on international and regional labour standards, the South African Constitution of 1996, and the national experience to make policy recommendations that will ensure workers are protected, firms are sustainable and labour markets operate well. Social justice and the democratisation of the workplace cannot be achieved if workers in non-standard employment are excluded from the labour relations system.
Keywords: Collective bargaining; Labor laws and legislation; Non-standard employment; Part-time employment; South Africa; Standard employment; Temporary employment; Temporary workers; Vulnerable workers

The integration of work and parenting: a comparative legal analysis - Rossouw, Elzaan (Stellenbosch University, 2018)
Given the importance of parental care to children, parents and broader society and the apparent conflict between work and adequate parental care, this study evaluates the legal facilitation of the integration of work and care across nine countries, including South Africa. The study recognises that legal operationalisation of the integration of work and care primarily takes place at domestic legislative level and shows that this happens against the backdrop of widespread recognition of the importance of the family and care at the international, regional and constitutional levels. The study builds on the reality that domestic legislation in this context consists of (a combination of) equality law and specific rights contained in employment standards legislation. The comparative review of equality law as applied in the area of the work-care conflict shows that, despite the potential and promise that equality law holds to facilitate the integration of work and care, this potential has not been realised and probably will not be in future. This necessarily shifts the focus to an approach founded on the extension of specific rights related to time off or leave, as well as flexible working, to employees in order to enable them effectively to combine work and caregiving. The comparative review of specific rights in this area leads to the conclusion that South Africa lags far behind certain developed and comparable developing countries in its legislative recognition of the importance of caregiving and in its subsequent level of employment rights extended to caregivers. Given the ample room for improvement, suggestions for legislative reform are made based on the comparative experience of other countries
URI: http://hdl.handle.net/10019.1/103776
Keywords: Child care services; Comparative law; Employee rights; Employment standards; Equity; Labour law; Labour legislation

Finding innovative solutions to extend labour law and social protection to vulnerable workers in the informal economy - Fourie, E. (North-West University, 2018)
The world of work has changed and this includes its fundamental design, purpose and coverage of employment. Work in the informal economy has increased and in many developing and middle income countries, work in the informal economy is the norm. In South Africa as well as in other developing countries informal economy workers do not enjoy sufficient protection in terms of labour and social protection measures. These workers are not recognised, regulated or protected by labour legislation or social protection measures and can be characterised by varying degrees of dependency and vulnerability. In countries where the informal economy is increasingly creating a parallel economic world to that of the formal economy, the extension of protection by facilitating the ability of these workers to bargain collectively and the role of national and local governments become increasingly important. Women workers in the informal economy are particularly vulnerable and face discrimination on multiple grounds and levels as gender inequalities in the informal economy cut across race and class lines. Linkages between informality, gender and poverty exists, namely: the poor are more likely to work in the informal economy; more poor women than non-poor women work in the informal economy and that there is a gender gap in earnings in the informal economy as women were earning less than their male counterparts and were less likely to be organised and have social protection. It is of the utmost importance that labour and social legislation accommodates and extends protection to informal economy workers. The larger the informal economy becomes, the greater the need becomes for social and labour protection. It will be impossible to provide these workers with the protection they deserve without legislative intervention. Furthermore, this intervention must be innovative and tailor-made to successfully extend labour and social protection to informal economy workers. When considering the protection of these workers it is also of importance to explore the design and implementation of innovative and tailor-made solutions, considering for example the nature of their work and their workplace. The focus of this study is specifically on distinctive vulnerable categories of women workers in the informal economy who are without adequate labour and social protection. These categories are domestic workers, informal traders and waste pickers. It is important to consider lessons learnt in other jurisdictions to adequately address the challenges in the informal economy. This study considers interventions in two leading developing jurisdictions, namely India and Brazil. Both these countries have a high prevalence of informal workers with inadequate labour and social protection. Labour law must thus meet the challenges posed by the realities of new forms of work. The important function of labour law to protect and promote the human dignity of workers will often result in a cross-over of various subsystems of the law. If we consider human dignity as an important component of labour law, then we need to consider an interdisciplinary approach and the promotion of such an approach. This approach will mean that labour law can no longer function in isolation and other branches of the law, such as social security law, corporate law, human rights and family law will increasingly have an impact on the human dignity of workers. When considering the future of labour law and specifically in relation to the labour and social protection of women in the informal economy, it is vital that the new framework is intrinsically linked to concepts such as democracy, social justice, freedom, and human rights. International and regional institutions are playing an increasingly important role in the empowerment of women, the promotion of equality and decent work for all women. This study identifies and critically considers the relevant international institutions and instruments, the impact of international standards, regional institutions and regional labour standards, particularly those of the African Union (AU) and the Southern Africa Development Community (SADC), and other global initiatives directed at the social and labour protection of women workers in the informal economy. The South African position with reference to domestic workers appears to provide an adequate regulatory framework in respect of the regulation of these workers; however, in practice there are various challenges, including the enforcement of the legislative provisions and a disregard for the notion of substantive equality. Although domestic workers enjoy some protection, waste pickers and informal traders as own-account workers without a distinctive employee-employer relationship are excluded from most labour and social protection measures and innovative and tailor-made solutions are required. The regulation of waste pickers and informal traders in South Africa is fragmented and lacks comprehensive and uniform legislation is absent. Voice and representation is of paramount importance to these women to ensure decent work. Enabling frameworks must be established to promote this. One of the most important objectives of organisation for women workers is to promote the recognition of these women and given their vulnerabilities experienced on various levels, this recognition must be wide and include recognition as workers, citizens and members of society that must be afforded human dignity on all levels. The position of the three categories of women workers was also considered in two jurisdictions, namely India and Brazil to distil best practices with reference to these workers. The research question of this study is: How can labour law and social protection measures provide vulnerable women workers in the informal economy with the appropriate protection to ultimately give effect to decent work? The main inquiry of this thesis, therefore, is to explore the issue of extending labour and social protection to these workers through the extension of existing labour and social security rights; including, where necessary, the design and implementation of innovative and tailor-made solutions.
Keywords: Decent work; Discrimination; Domestic worker; Gender equality; Informal economy; Informal trader; Labour and social protection; Social assistance; Social justice; Social security; Tailor made provisions; Waste pickers; Women; Worker organisations

The impact of threshold agreements on the organisational rights of minority trade unions - Esitang, Temogo Geoffrey (University of Pretoria, 2017)
The rights of freedom of association, to organise and to bargain collectively are recognised internationally and form part of the constitutional framework of progressive and democratic states. The full enjoyment of these rights by trade unions often is hindered by the imbalance in the power relations between the employer and the representatives of the workers, hence the need for statutory intervention. The Labour Relations Act 66 of 1995 (LRA of 1995) postulates a collective bargaining regime which is voluntarist in nature and strengthens its effectiveness through a set of organisational rights and the right to strike. Incidentally, the current statutory framework for the enjoyment of organisational rights has had a direct impact on the enjoyment of the right to freedom of association and the right to organise. It is accepted that possession of the right to collective bargaining is internationally recognised as the basis of the authority to set thresholds of representivity in the workplace. The organisational rights framework in this context has been directly impacted upon. It is this direct impact that necessitates an enquiry to determine whether South Africa’s framework on the acquisition of organisational rights conforms to international standards set by the ILO and the Constitution, 1996. This thesis argues that the policy choice of the South African labour relations system in respect of some of the consequences of majoritarianism insofar as representation in individual cases is concerned does not necessarily foster the ideals of the Constitution, 1996 and the principles of international labour standards. The model of democracy as envisaged in the Constitution, 1996 is not one that promotes exclusivity. However, the effect of section 18 of the LRA of 1995, which allows threshold agreements, arguably may foster such exclusivity in the workplace. This situation has resulted in industrial democracy being a terrain of endless conflict between employers and labour, even more among trade unions themselves. As a result, the rivalry between unions in workplaces is exacerbated. The original intent behind the organisational rights of trade unions and their right to strike was to bolster their capacity to bargain collectively. It was meant to get them to focus on collective bargaining gains they can secure and to bargain more effectively. However, the current framework that favours majority trade unions has the effect of minority trade unions generally finding their existence threatened and their being systematically excluded from the acquisition of organisational rights. This study questions the power of majority trade unions to enter a collective agreement with an employer in the workplace and set unjustifiable thresholds of representivity in respect of organisational rights. This arrangement creates a hurdle in respect of the provisions of the LRA that seek to promote industrial democracy, the enjoyment of the rights to freedom of association, to organise and to engage in collective bargaining. Recent amendments to the LRA of 1995 are an attempt to mitigate the effect of sections 18 and 20 on the enjoyment of organisational rights. The CCMA, inter alia, has been granted powers to grant organisational rights to trade unions that do not meet the set threshold in terms of the empowering provisions of the LRA of 1995 if they meet certain requirements. However, these amendments do not go far enough to prevent employers and majority trade unions from continuing to set unjustifiable thresholds that can have potential to replace the determinations of the CCMA. Therefore, the study discusses the question whether the provision in the LRA of 1995 on the setting of thresholds of representivity for the acquisition of organisational rights and the concomitant amendments are in line with the democratic model envisaged by the Constitution, 1996 and to international labour standards which recognise the rights to freedom of association of minority trade unions. This research concludes by advancing recommendations pertaining to threshold agreements and the rights of minority trade unions and to what extent it is justifiable to permit them to enjoy them.
URI: https://repository.up.ac.za/handle/2263/68000
Keywords: Collective bargaining; Employer; Employeur; Labour Relations Act; Representatives workers

Identification of the parties to the employment relationship: An appraisal of teleological interpretation of statutes - Van Staden, Marthinus Jacobus (University of Pretoria, 2017)
The study, entitled “Identification of the parties to the employment relationship: an appraisal of teleological interpretation of statutes”, is a legal-interdisciplinary doctrinal investigation situated within the fields of labour law and the interpretation of statutes. It concerns itself with the proper interpretation of labour legislation in general and the interpretive question as to who should be party to the employment relationship in particular, within the context of the advent of constitutionalism and the proliferation of and the increase in the importance of labour legislation. In law, meaning-generation is a function of statutory interpretation and every application of a text to particular circumstances entails interpretation. The protection extended by labour legislation is only extended to those persons who are defined as “employees”. The study describes the teleological model of statutory interpretation, which aims to give effect to the purpose of a legislative provision in light of constitutional values. The study explores the five elements of (teleological) interpretation that should be considered when interpreting concepts such as “employee”: the text, the context, the telos (or values), the history and the comparative dimension. The chief findings of the study includes: that legislation has become an indispensable source of contemporary labour law; that the courts have adopted a teleological approach to the interpretation of statutes; that the courts have, in interpreting the term “employee”, adopted a teleological approach to the interpretation of statutes; and that the interpretations advanced by the courts have not had the profound effect envisaged by the Constitution on the transformation of society.
URI: https://repository.up.ac.za/handle/2263/65631
Keywords: Employment relationship; Labour law; Parties

Force Majeure, Change of Circumstances and Termination of Contract - Han, Shiyuan (Journal of Law, Society and Development, 2016)
It is impossible to draw a distinct line between force majeure and change of circumstances, because the two overlap. In order to regulate both force majeure and change of circumstances, the United Nations Convention on Contracts for the International Sale of Goods (CISG) has adopted a unified model in article 79, whereas Chinese law adopts a dual model by treating them as different things and regulating them in different articles. Where the purpose of a contract becomes impossible to achieve because of a force majeure and both the CISG and Chinese Contract Law (the CCL) adopt the same model of termination of the contract, the contract should be terminated by one party with a notice to the other party instead of ipso facto avoidance. In a case of a change of circumstances, in order to terminate the contract, both the CISG and the CCL actually follow the path of raising an action by a notice of avoidance or termination to theother party. Both approaches have their merits and demerits but the differences between them in practice are not as large as presumed. Where force majeure and change of circumstances overlap each other, possible ways for termination of the contract are for a party either to choose their preferred solution or to follow the lex specialis derogat generali. The latter way is preferred in this article; and while in an action for termination the judge may balance the interests of both parties in making a final decision, the uniform application of the law, the safety of the transaction and the fairness of the judgment may be ensured in so doing.
Keywords: CISG; Change of circumstances; Chinese Contract Law; Force majeure; Gestaltungsklagerecht; Termination

Protection of agency workers in South Africa : an appraisal of compliance with ILO and EU Norms - Aletter, Candice Joy (University of Pretoria, 2016)
This thesis is a policy-based study of the regulation of agency work in South Africa. It is set against the contextual background of a recent legislative overhaul and an increase in the number of precarious workers. The study aims to appraise the extent to which the South African regulatory framework complies with international norms in respect of agency work. The research considers how German and Namibian regulation might improve the current model of the regulation of agency work in South Africa. The study identifies the purpose of labour law in South Africa as offering diversified rights as well as being economic in nature. The premise upon which the thesis is based is a social justice approach to the function of labour law. An analysis of ILO and EU regulations on agency work is conducted, and identifies a combined list of norms in respect of the protection of agency workers. South Africa?s labour law policy approach is explored together with the amended regulation on agency work. A comparison is drawn with foreign countries? regulations and policy approaches: the appraisal identifies shortcomings in South Africa?s regulatory model. The study focuses on the evolutionary improvement of agency workers? protection based on international approaches. The research culminates by formulating an amended model for the regulation of agency work in South Africa, in which these proposed adaptations seek to remedy the shortcomings which were observed in the appraisal process.
URI: https://repository.up.ac.za/handle/2263/60060
Keywords: Agency work; EU Regulations; ILO; Labour law; South Africa

Regional Labour Standards in the SADC: Is It Possible, Given the EU Experience? - Smit, Paul (Journal of Law, Society and Development, 2015)
Globalisation and the increasing movement of capital and labour across international borders, with the exception of migrant workers who are facing major obstacles due to immigration laws, are creating a situation where laws in general and labour laws in particular are acquiring an international character. International bodies such as the United Nations, the International Labour Organisation and the European Union have adopted various international norms and standards to which most countries have agreed and which have established minimum international standards for basic universal human rights and worker rights. The Southern African Development Community is a transnational organisation that has also adopted certain basic norms and standards in its Treaty, Charter on Fundamental Social Rights and various protocols that are applicable to all citizens within the Community. In this contribution, the concept of transnational labour relations is considered. The different international approaches towards transnational labour relations are evaluated, as is the manner in which the European Union approached the integration of regional labour standards. The author seeks to establish what the Southern African Development Community can learn from the European Union’s experience and in what way a transnational labour relations system or regional labour standards regime for the Southern African Development Community can be established.
Keywords: Regional integration; Transnational labour relations (TNLR); international law; labour rights; regional labour standards; social rights

Employee participation and voice in companies: a legal perspective - Botha, Monray Marsellus (North-West University, 2015)
Recently, South African company law underwent a dramatic overhaul through the introduction of the Companies Act 71 of 2008. Central to company law is the promotion of corporate governance: companies no longer are accountable to their shareholders only but to society at large. Leaders should direct company strategy and operations with a view to achieving the triple bottom-line (economic, social and environmental performance) and, thus, should manage the business in a sustainable manner. An important question in company law today: In whose interest should the company be managed? Corporate governance needs to address the entire span of responsibilities to all stakeholders of the company, such as customers, employees, shareholders, suppliers and the community at large. The Companies Act aims to balance the rights and obligations of shareholders and directors within companies and encourages the efficient and responsible management of companies. The promotion of human rights is central in the application of company law: it is extremely important given the significant role of enterprises within the social and economic life of the nation. The interests of various stakeholder groups in the context of the corporation as a “social institution” should be enhanced and protected. Because corporations are a part of society and the community they are required to be socially responsible and to be more accountable to all stakeholders in the company. Although directors act in the best interests of shareholders, collectively, they must also consider the interests of other stakeholders. Sustainable relationships with all the relevant stakeholders are important. The advancement of social justice is important to corporations in that they should take into account the Constitution, labour and company law legislation in dealing with social justice issues. Employees have become important stakeholders in companies and their needs should be taken into account in a bigger corporate governance and social responsibility framework. Consideration of the role of employees in corporations entails notice that the Constitution grants every person a fundamental right to fair labour practices. Social as well as political change became evident after South Africa's re-entry into the world in the 1990s. Change to socio-economic conditions in a developing country is also evident. These changes have a major influence on South African labour law. Like company law, labour law, to a large extent, is codified. Like company law, no precise definition of labour law exists. From the various definitions, labour law covers both the individual and collective labour law and various role-players are involved. These role-players include trade unions, employers/companies, employees, and the state. The various relationships between these parties, ultimately, are what guides a certain outcome if there is a power play between them. In 1995 the South African labour market was transformed by the introduction of the Labour Relations Act 66 of 1995. The LRA remains the primary piece of labour legislation that governs labour law in South Africa. The notion of industrial democracy and the transformation of the workplace are central issues in South African labour law. The constitutional change that have taken place in South Africa, by which the protection of human rights and the democratisation of the workplace are advanced contributed to these developments. Before the enactment of the LRA, employee participation and voice were much-debated topics, locally and internationally. In considering employee participation, it is essential to take due cognisance of both the labour and company law principles that are pertinent: the need for workers to have a voice in the workplace and for employers to manage their corporations. Employee participation and voice should be evident at different levels: from information-sharing to consultation to joint decision-making. Corporations should enhance systems and processes that facilitate employee participation and voice in decisions that affect employees. The primary research question under investigation is: What role should (and could) employees play in corporate decision-making in South Africa? The main inquiry of the thesis, therefore, is to explore the issue of granting a voice to employees in companies, in particular, the role of employees in the decision-making processes of companies. The thesis explores various options, including supervisory co-determination as well as social co-determination, in order to find solutions that will facilitate the achievement of employee participation and voice in companies in South Africa.
Keywords: CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Corporate law; Disputes; Economic democracy; Employee participation; Empowerment; Fairness; Industrial democracy; Joint decision-making; Labour law; Matters of mutual interest; Shareholders; Social justice; Stakeholders; Workplace forums

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions

Employees Contract of Employment and Wrongful Dismissal From Service - Ugbele, Sunday; Utobo, O. J. (African Journal of Politics and Administrative Studies, 2014)
Contract of employment was long acknowledged as a subject of genuine and voluntary agreement whose construction or determination should be founded on due notice of the parties thereto. Action for wrongful dismissal would lie if an employment was disturbed, interfered or meddled with, in defiance of the rights of the parties under the contract. The objective of this study was, among others, to determine what constituted a valid contract of employment and remedies for wrongful dismissal. The qualitative and documentary method of data collection was adopted by reference to relevant literature and statutory authorities. From the data gathered, and content analyzed, we found that no law could foreclose an employment from determination, nor could an irregular or wrongful dismissal stand. It was recommended, inter alia, that beside the need to repeal the Public Officers (Protection) Act, both the employer and employee should, in their official dealings, respect the sanctity of their contract, and permit reasonable future modifications thereto as could lawfully enhance the life of the contract and their legitimate desires.

New Frontiers on Legal Enforceability of Collective Agreements in Nigeria - Zechariah, Matthias (Current Jos Law Journal, 2013)
The objectives of this research paper are: to examine the status of collective agreements under the common law; highlight impacts of statutory intervention on common law perception of collective agreements, and discuss how the National industrial Court (NIC) and the Constitution of the Federal Republic of Nigeria 1999 (as altered) have broadened the horizon of enforceability of collective agreements in Nigeria. Reliance is placed principally on statutes, judicial decisions, textbooks written by learned authors as well as international best standard and practices championed by the International Labour Organization (ILO) and practices in some foreign jurisdictions. The ﬁndings of the research were that under the common law, collective agreements are ordinarily not binding, they are considered as a ‘gentleman's agreement‘, a product of a trade unionist's pressure, binding only in honour or on the goodwill of the parties thereto, unless and until it is incorporated expressly or impliedly into the contract of employment. However, statutory intervention has slightly altered the common law notion of collective agreements, e.g. where the Minister of Labour and Productivity is empowered to declare, by order, that part or the whole of an agreement deposited in his ofﬁce is binding on the parties. Furthermore, with the enactment of the NIC Act and the listing of the NIC in the 1999 Constitution as a superior court of record (following the alteration of the Constitution, necessitated by the N.U.E.E. V BPE case), the Court now has exclusive jurisdiction to adjudicate on a wide range of labour matters, industrial relations and application of international best practices such as the standard and principles of the International Labour Organization (ILO), and practices in foreign jurisdictions. It has been argued that the enforceability of collective agreements is in tandem with international best practices, which the NIC can readily give effect to, if it is pleaded and established/ proved as a fact. This has invariability expanded the frontiers of enforceability of such agreements. Therefore, the common law position on the status of collective agreements has been rendered otiose and obsolete, giving way to the sparkling provisions of enforceability guaranteed by the NIC Act and the Constitution respectively. Notwithstanding, it is highly recommended that parties to a collective agreement should expressly state their intention whether or not to be bound; the duration of the agreement should be stated and whether, and when, it should, be reviewed; experts and other stakeholders should be properly consulted before an agreement is entered into; an arbitration clause may be included in case a party breaches its own part of the agreement. Industrial democracy ought to be promoted in all sectors. Strikes and lock outs should be used only as a last resort for enforcing compliance with a collective agreement, because these industrial actions cause devastating effects on the economy and on the lives of the citizenry generally.
Accepted: 2017-08-16T13:03:49Z

Disability, discrimination and equal opportunities : a comparative labour law study - Harmse-Truter, Laurentia (University of Johannesburg, 2012)
This study aims to investigate the different ways in which the position of people with disabilities can be addressed. Antidiscrimination legislation can play a very important role. Efforts to create equal opportunities must, however, not be limited to legislative initiatives and policy declarations. There is an urgent need for education and training of this minority group. 7 Systematic efforts to heighten public awareness of civil rights and in particular the recognition of the rights of the disabled community are imperative. This study aims to bring home the truth that "disability rights are an idea and ideal whose time has come. ,, When addressing the issue of disability discrimination (or for that matter any kind of discrimination) several principles need to be addressed, the most important being the following: The meaning of the concept of "equality" needs to be established. The fact that all people are equal, does not necessarily mean that all people must be treated the same. When speaking about disability discrimination one must know who forms part of the protected class. For that reason the first issue that must be addressed is the definition of "disability": This leads to the next question, namely which individuals should be protected by anti-discrimination laws and should they benefit from affirmative action measures? What is meant by the term "discrimination"? Is it at all permissible to distinguish between groups of people and, if so, when and which standards are to be applied? What role can anti-discrimination legislation fulfil in the struggle for equality? When dealing with anti-discrimination legislation, what is required in order to prove discrimination and what remedies must be available to an aggrieved party? Normally, in case of criminal action proof is required beyond reasonable doubt and in case of civil action on the balance of probabilities. 10 Civil action offers more effective remedies, but should it be punitive in nature (by awarding damages to the aggrieved party) or non-punitive (by putting the aggrieved party in his/her "rightful place")? What sort of enforcement mechanism is needed? Is it a task for the ordinary tribunals or rather a special body created for that purpose? What defences should be available to an employer accused of discriminatory practices? Who should benefit from enforcement? Only the individual victim or all members of that group? Is anti-discrimination legislation sufficient or is something in addition called for? If positive measures are required, what form must these measures take? This study will address these questions specifically with relation to people with disabilities.The "equality principle" will first be studied. Thereafter the concept of "disability" will be defined. There is a movement away from a medical model of disability towards a social model that takes account of the disabling effects of attitudes and structural barriers on the position of disabled people. Then the concept of "discrimination" will be addressed. Discrimination has many different forms and can take place in different contexts In the following chapter possible solutions to the problem of disability discrimination will be raised. Thereafter follows an important comparative analysis of different jurisdictions on international, supra-national and national level. Different jurisdictions have reached different stages in addressing this problem. The factual analysis of each jurisdiction will include the existence of any anti-discrimination legislative measures, the scope of the protected class, applicable employment provisions, defences available to employers, and the success achieved in addressing the problem. The contentious issue of affirmative action measures will also be addressed. By drawing inferences from the comparative study, suggestions will be made for future developments in South Africa. The conclusion is reached that it is imperative for South Africa to draft disability anti-discrimination legislation that takes account of the needs of this minority group. Legislative initiatives, however, are not enough and must be supported by various programmes aimed at the disabled themselves and the community that they live in. Only then can human rights become a reality also for people with disabilities.
Keywords: Comparative law; Discrimination; Employment; Labour law; People with disabilities

The legal implications of harmonising labour laws in the Southern African Development Community (SADC) region - Okharedia, Akhabue Anthony (University of South Africa, 2012)
The purpose of this research is to explore the need for, and the legal implications of, harmonising labour laws in the Southern African Development Community (SADC). Chapter One highlights a number of factors that call for the harmonisation of labour laws in the SADC region and discusses some of the reasons why labour laws are not well developed in the region. The influence of globalisation on labour standards in southern Africa and the influence of regionalism on the harmonisation of labour laws are discussed at length. The inference that could be drawn from this discussion is that for a regionalisation process in southern Africa to be successful, there is an urgent need to harmonise the region’s labour law system. This thesis confirms that Southern Africa has many lessons to learn from the regional harmonisation of labour law in the European Economic Community and the current European Union. The implementation of international labour standards in southern Africa is investigated. The main areas examined include (1) freedom of association, (2) collective bargaining, (3) forced labour and (4) discrimination. The findings of this investigation show that there is no uniformity in the implementation of International Labour Organisation (ILO) standards in the SADC region and, therefore, it is recommended labour law should be harmonised in terms of ILO standards. In respect of the benefits to be derived from the harmonisation process, an empirical investigation was conducted in the SADC region and the following is recommended: the harmonisation of labour law in the SADC region will help with the implementation of ILO standards, protection of workers against the economic power of employers in the workplace and maintaining similar benefits for migrants in the region.
Keywords: Child labor; Collective bargaining; Compulsory labour; Discrimination in employment; Discrimination in the work environment; Droit du travail; Forced labour; Freedom of association; Harmonisation; International Labour Organization; International Labour Standards; Labour law; SADC

The Protection of Privacy in the Workplace: A Comparative Study - Gondwe, Mimmy (Stellenbosch University, 2011)
The importance of privacy lies in the fact that it represents the very idea of human dignity or the preservation of the ‘inner sanctum’. Not surprisingly, however, operational concerns of employers and technological developments combine continuously to challenge the preservation of privacy in the workplace. Employees the world over are exposed to numerous privacy invasive measures, including drug testing, psychological testing, polygraph testing, genetic testing, psychological testing, electronic monitoring and background checks. Hence, the issue at the heart of this dissertation is to determine to what extent privacy is protected in the South African workplace given advancements in technology and the implications (if any) for the right to privacy as such. A secondary aim of the dissertation is to attempt to provide a realistic balance between the privacy concerns of employees and the operational needs of employers in this technological age. As such the main focus of dissertation falls within the sphere of employment law. In order to provide an answer to the research issue discussed above, the dissertation addresses five ancillary or interrelated issues. First, the broad historical development of the legal protection of privacy is traced and examined. Second, a workable definition of privacy is identified with reference to academic debate and comparative legislative and judicial developments. Third, those policies and practices, which would typically threaten privacy in the employment sphere are identified and briefly discussed. Fourth, a detailed evaluation of the tension between privacy and a number of selected policies and practices in selected countries is provided. More specifically, the dissertation considers how these policies and practices challenge privacy, the rationale for their existence and, if applicable, how these policies and practices – if necessary through appropriate regulation – may be accommodated while simultaneously accommodating both privacy and the legitimate concerns of employers. The selection of these practices and policies is guided by two considerations. At the first level the emphasis is on those challenges to privacy, which can be traced back to technological developments and which, as such, foster new and unique demands to the accommodation of privacy in the workplace. The secondary emphasis is on those policies, which are representative of the fundamental challenges created by new technologies to privacy. To effectively address the above issues the dissertation uses the traditional legal methodology associated with comparative legal research, which includes a literature review of applicable law and legal frame work and a review of relevant case law and a comparative study of selected foreign jurisdictions.
URI: http://hdl.handle.net/10019.1/17849
Keywords: Privacy infringements; Privacy protection; Right of privacy

Public employment and the relationship between labour and administrative law - Loots, Barbara Evelyn (University of Stellenbosch, 2011)
The focus of this study is the rights-based normative overlap of labour and administrative law in public employment. As the judiciary appeared to be unable to agree on a unified approach to the application of the rights to fair labour practices and just administrative action to public employment, it was clear that the complexity and multi-dimensional character of the debate required analysis of existing approaches to the regulation of the public employment relationship. The following initial research question was formulated: To what extent does (and should) the constitutionalised rights to fair labour practices (s 23) and just administrative action (s 33) simultaneously find application in the regulation of public employment relationships? In answering this question, certain realities had to be acknowledged, the most important being that the debate in question jurisprudentially revealed itself to be a jurisdictional turf-war between the Labour and High Courts, rather than proper consideration of the relevant substantive arguments and underlying normative considerations. This called for an additional dimension to be added to the research question, namely consideration of the extent to which the ss 23 and 33 rights are informed by variable and possibly different normative principles and whether these rights allow for cooperative regulation of public employment in accordance with the doctrine of interdependent fundamental rights. This became the primary focus of the study. In an attempt to simplify the debate, a deliberate decision was taken to limit the scope of the normative study to South Africa with its own historic influences, structures and constitutional considerations. The study shows that both labour and administrative law (as constitutionally informed) share concern for equity-based principles. This is evident from the flexible contextually informed perspectives of administrative law reasonableness in relation to labour law substantive fairness, as well as a shared concern for and approach to procedural fairness. Once simplified, and in the absence of any undue positive law complexity, the public employment relationship, at both a normative and theoretical level, furthermore shows no substantive status difference with private employment relationships. It is, however, accepted that there are job and sector-specific contextual differences. In the absence of substantive normative conflict between these branches of law and in the absence of a fundamental (as opposed to contextual) difference between public and private employment, there appears to be no reason to ignore the constitutional jurisprudential calls for hybridity, otherwise termed the doctrine of interdependence. The idea of normatively interdependent rights expresses the Constitution’s transformative vision (through the idea of flexible conceptual contextualism) and recognises that human rights may overlap. This also means that where such overlap exists, rights should be interpreted and applied in a mutually supportive and cooperative manner that allows for the full protection and promotion of those rights. In giving expression to the interdependent normative framework of constitutional rights, these norms (absent any substantive rights-based conflict) should then be used by the judiciary as an interpretative tool to align specific labour law and general administrative law in the regulation of public employment relationships.
URI: http://hdl.handle.net/10019.1/6683
Keywords: Administrative law; Employment law; Labour law

Labour law implications of the transfer of an undertaking - Smit, Nicola (University of Johannesburg, 2009)
This thesis provides a comprehensive analysis of the legal, social, and economic consequences of business transfers on employment contracts, focusing on South African law and its comparison with international standards. It critically evaluates the automatic transfer of employment contracts, the protection of employee rights, and the legal complexities surrounding insolvent undertakings.
Keywords: Labour law; Labour legislation; Transfer (Law)

Alternative means to regulate the employment relationship in the changing world of work - Vettori, Maria-Stella (University of Pretoria, 2006)
Advancing technology has caused rapid and dramatic changes in the world of work. Labour law systems grounded in the industrial era, with their emphasis on collective bargaining, are not suitable in today’s world of work. Throughout the world, the ‘atypical employee’ is replacing the standard or typical employee whose terms and conditions of employment were generally regulated by collective agreements. Atypical employee’s terms and conditions of employment generally are not regulated by collective agreements. World– wide trends in the decentralisation of collective bargaining, decollectivisation and individualisation of the employment relationship have contributed to a decline in trade union power and influence. Consequently the number of workers covered by collective agreements has decreased. Collective bargaining has been rendered less effective because of the changing the world of work. The South African labour law system places a huge emphasis on collective bargaining, particularly at industry level, for the protection of employee interests. Given these trends in the changing world of work, the appropriateness of this emphasis on industry or central level collective bargaining is questioned. The vacuum left by the inadequacy and inability of trade unions to protect employee interests in a comprehensive manner by means of collective bargaining, needs to be addressed. The following alternative means of protecting employee interests are considered: (i) The socialisation of the law of contract; (ii) the interpretation given to the constitutional right to fair labour practices; and (iii) the role of good corporate governance and corporate social responsibility. These alternative means of addressing legitimate employee interests could play a role in filling the vacuum created by trade union decline. The South African law of contract is capable of bridging the gap between law and justice by the application of the concepts of good faith and public policy, so that employment contracts may take cognisance of employee interests despite the imbalance of power between employer and employee. The protection of worker interests by means of the constitutional right to fair labour practices depends on the judge’s interpretation of what is fair. Implementation of good corporate governance codes can be influential in protecting and promoting employee interests.
Keywords: Atypical employee; CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Decentralization; Decollectivisation; Fordism; Individualization

Theories of the company, employees and takeover regulation - Johnston, Andrew (European University Institute, 2004)
Keywords: Consolidation of corporations; European Union countries; Labor laws and legislation; Merger of corporations; Social policy

Self-employment and the personal scope of labour law : comparative lessons from France, Italy, Sweden, the United Kingdom and the United States - Engblom, Samuel (European University Institute, 2003)
The past two decades has seen a growing interest, from both policy makers and scholars, in the legal regulation of work performed by self-employed workers. Increases in non-agricultural selfemployment in industrialised countries, together with political and ideological shifts, have fuelled interest in self-employment as a means of increasing employment. The attractions of selfemployment are manifold. To firms, self-employment is part of a two-fold change in the way firms operate: the move towards more flexibility as to the size and composition of the workforce, marked by an increased use of atypical workers and the disintegration of firms by arranging production through outsourcing, subcontracting and franchising. To workers, self-employment offers the greater autonomy connected with being their own boss, a chance of higher returns, or, at least, opportunities of gainful employment in times of high unemployment. To governments, self-employment has been seen as a means of increasing the number of small businesses, supposedly beneficial to the creation of new employment. Encouraging and removing barriers to self-employment is, therefore, a priority for many governments.
Keywords: Labor laws and legislation